Analysis of Energy Transportation and Distribution in Indonesia - Suganda P Simanjuntak; Rismen Sinambela; Leonard Lisapaly (TURBO [Tulisan Riset Berbasis Online], 2025)
Energy transportation and distribution are crucial components in the national energy system, serving as the main link between energy sources and consumers. The efficiency of both systems is crucial to maintain the stability of energy supply and minimize energy loss during the distribution process. This study aims to explore the importance of energy transportation and distribution in the context of national energy security and the geographical and energy infrastructure challenges in Indonesia. Using a literature study method, this study collects and analyzes literature from various academic sources and relevant reports. The results show that an efficient energy transportation and distribution system plays a major role in reducing the energy gap between regions, expanding energy access to remote areas, and supporting sustainable economic development. In addition, Indonesia's geographical challenges as an archipelagic country, such as the distance between islands and population inequality, widen the energy infrastructure gap between the western and eastern regions. Investment in energy infrastructure development, especially in disadvantaged areas, and the integration of renewable energy are important steps in strengthening national energy security. This study concludes that in order to achieve better and more equitable energy security, inclusive and sustainable energy infrastructure development policies and strategies are needed.